Peningkatan Kualitas Pembelajaran Explanation Text Menggunakan Model Problem Based Learning Berbasis Lesson Study - Ananda Rival Prakoso; Putu Seriardana; Luh Diah Surya Adnyani (Jurnal Ilmiah Pendidikan Profesi Guru, 2021)
Students' problems in writing explanatory texts start from understanding the structures of explanatory texts, determining topics, making themes so that they become an essay outline, to developing an essay outline that is directed at making texts. In addition, students' interest in writing is still low. The purpose of this study was to analyze the problem-based learning model on the quality of explanation text learning in English subjects for high school students. This research is qualitative. This study uses a problem-based learning model based on lesson study. There are three stages carried out in lesson study activities, namely: planning (plan), implementation (do), and reflection (see). The subjects selected were 11th-grade students in high school. The results showed that giving the text model to students, dissecting the text, and summarizing the text could be followed by students smoothly, however, 15 minutes to respond to the content of the video presented was felt to be lacking. In general, student participation was good during the learning activities, and the skills that were trained were also successfully seen from the worksheet results. Based on the results of the study, it can be concluded that the problem-based learning model based on lesson study is considered effective in teaching explanation text in high school students.